Tinjauan Penerapan Prosedur Audit Atas Utang Usaha pada PT XYZ Oleh KAP Ramli & Rekan - Adinda Athaya Salwa; Khaila Putri Amalia; Shafira Elyana; Susan Leoni; Eka Merdekawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the implementation of audit procedures on accounts payable at PT XYZ by KAP Ramli & Rekan, with a focus on compliance with Auditing Standards and effectiveness in detecting material misstatements. Accounts payable are a key component of financial statements representing the company’s obligations to suppliers, requiring accurate presentation for assessing liquidity and capital structure. The study applies a descriptive qualitative method, collecting primary data through interviews with audit staff at KAP Ramli & Rekan and secondary data from relevant literature. The findings show that the audit procedures comply with professional standards, covering comprehensive stages including engagement acceptance, audit planning, risk and materiality assessment, and substantive testing. The planning process incorporates the COSO framework for evaluating internal control, establishes audit objectives based on the five management assertions, and utilizes ATLAS software and Microsoft Excel. KAP Ramli & Rekan apply control testing and substantive procedures, including external confirmations, inspection of supporting documents, review of aging payables, and subsequent payment testing. Risk assessment indicates low inherent and control risks, while detection risk is mitigated through substantive procedures. Overall Materiality is set at 60% of revenue and profit before tax, Performance Materiality at 3% of Overall Materiality, and Threshold Materiality at 3% of Performance Materiality. The study concludes that the audit procedures implemented by KAP Ramli & Rekan align with applicable Auditing Standards and are effective in addressing audit risks related to accounts payable. The implications highlight the importance of enhancing audit quality practices, particularly the effectiveness of planning and internal control evaluation in accounts payable audits.